Visualisasi Garap Cerita dan Struktur dalam Tari Wireng di Mangkunegaran - Hadi Subagyo (Greget, 2010)
Broadly speaking, the Wireng dance genre from the Mangkunegaran can be divided into three groups or categories according to the source of the story presented, namely Wireng Purwa, Wireng Madya, and Wireng Panji or Gedhog. From a visual point of view, the costumes characterize each of these categories of performance. The visualization of the particular style of Wireng dance uses structures known as Maju Beksan, Beksan, and Mundur Beksan. In addition, the structure of the wireng dance is formed through the composition of the music and the arrangement of the dance patterns.Keywords: Wireng, story, and structure.